IDENTIFIKASI KESALAHAN SISWA SMP DALAM MENYELESAIKAN SOAL KEMAMPUAN PENALARAN MATEMATIK PADA MATERI BANGUN RUANG SISI DATAR DENGAN ANALISIS KESALAHAN NEWMAN - Lestari, Atika Sri; Aripin, Usman; Hendriana, Heris (IKIP Siliwangi, 2018)
The Reasoning is the process of thinking to take a conclusion based on observations. The reasoning is very useful for dealing with problems in daily life. Once the importance of reasoning in life, so that the reasoning ability continues to be developed, one of them through the academic field. Because of the importance of reasoning ability for students, it is necessary to analyze what errors are done by students in solving the problem of reasoning ability. So that in the future the students' mathematical reasoning ability can be better. The type of research is descriptive qualitative research. This research was conducted in SMP Negeri 1 Margaasih with 15 students. The data collected is in the form of test and interview data, then data will be processed by Newman error analysis theory. The result of the research shows that the students' make a mistake because the students' lack of understanding on the concept, the lack of students' knowledge in reading, understanding and answering questions, and the students are not accustomed to working on the problem of mathematical reasoning ability. The most common type of Newman error in solving the problem of mathematical reasoning is errors in notation writing, and the error-prone reasoning indicator is an indicator to check the validity of an argument.